El impacto en la gestión de la cadena de suministros en las empresas de fabricación de productos metálicos para uso estructural en Santa Anita durante los años 2020-2021 - Pajares Domínguez, Daniel (2023)
In this paper the impact on supply chain management within the manufacturing sector of metal products for structural use between the years 2020-2021 was analyzed. In the first chapter the problematic situation it faces is detailed, which is mainly linked to the world productive deficit, generated by the scarcity of raw materials and government policies, which, through progressive restrictions, hinder free trade. Consequently, all the processes involved in the supply chain from the suppliers to the dispatch are affected by this context. In the second chapter, the analysis of the supply chain will be deepened, through a more detailed explanation of each section that makes it up: supplier, supply, manufacturing, and dispatch. In addition, the background will be detailed through the funnel method to include significant and relevant studies that reinforce the objective of the research. Later, the concept and phenomenon of the bullwhip effect will be integrated, as its name indicates, this effect is like a bullwhip, since a slight change can generate a large movement in the result, in other words, a fluctuation in demand, prices, times, inventories or orders can cause a swing in the supply chain much larger. Through an explanatory analysis in which a causal relationship of the affectation brought about by the health crisis will be sought, various companies in this sector in the Santa Anita district will be evaluated. Among the main findings obtained, it was found that there is a direct relationship between the rise in prices of the most important inputs, such as oxygen and metals, and the increase in the deficit in the profitability of the company, likewise, it is verified that there is an impact Negative both around suppliers and in manufacturing due to the scarcity of raw materials.